APPLICATION OF MATERIAL FLOW COST ACCOUNTING AND GREEN ACCOUNTING TO ENVIRONMENTAL PERFORMANCE - Holiawati Holiawati; Erick Valentine; Suripto Suripto (ZILLZELL MEDIA PRIMA, 2025)
Rapid economic growth and increased industrial activity have significantly impacted the environment. This issue demands greater responsibility from companies in the energy sector in managing the environmental impact of their business operations. This study aims to examine the application of Material Flow Cost Accounting (MFCA) and Green Accounting on Environmental Performance. The research uses a sample of energy sector companies during the 2022-2023 period. The sample was selected using the purposive sampling method, resulting in 47 energy sector companies over two years (2022-2023), yielding 94 observational data points. Hypothesis testing in this study employs Panel Data Regression Analysis using E-views software. The results demonstrate that Material Flow Cost Accounting (MFCA) has a positive effect on Environmental Performance, whereas Green Accounting does not significantly influence Environmental Performance.